2019
DOI: 10.1038/s41598-019-55265-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bacteria-Immobilized Cellulose Acetate/Poly(ethylene oxide) Nanofibrous Membrane for Wastewater Treatment

Abstract: In this study, electrospun cellulose acetate - poly(ethylene oxide) nanofibrous membrane was found to be unique in immobilizing bacterial cells. Here, removal of methylene blue in aqueous media was achieved by using isolated species of bacteria (Bacillus paramycoides) from industrial wastewater and immobilized on cellulose acetate- poly(ethylene oxide) nanofibers using DMSO as a solvent. The decolorization time was varied from 0 to 72 h, different dye concentrations from 20 to 200 mg/L and bacterial cells coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Despite the removal of azo dyes from effluents using conventional treatments, such as flocculation, membrane filtration, photocatalysis and adsorption 5 8 , microbial decolorization is a cheaper and eco-friendly accepted technique for the removal of dyes compared to conventional physical and chemical methods 3 , 9 . Hence, most current studies on the degradation of azo dyes are mainly focused on microbial degradation using filamentous fungi and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the removal of azo dyes from effluents using conventional treatments, such as flocculation, membrane filtration, photocatalysis and adsorption 5 8 , microbial decolorization is a cheaper and eco-friendly accepted technique for the removal of dyes compared to conventional physical and chemical methods 3 , 9 . Hence, most current studies on the degradation of azo dyes are mainly focused on microbial degradation using filamentous fungi and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…They found that removal efficiency of bacteria/PEO nanofibers was higher than of bacteria/PVA. Zamel et al incorporated bacteria (Bacillus paramycoides) into CA/PEO nanofibers by electrospinning technique and used for the decolorization of MB dye [210]. The removal efficiency of bacteria/CA/PEO nanofibers was 93% at first cycle and was decreased to 44% after the 4th cycle.…”
Section: Epnfs/metal Oxides Nanocompositesmentioning
confidence: 99%
“…This immobilization system has been reported to be better than the free cell system as it offers a high loading rate and inhibits biomass washout. The other advantages of using this technology include higher stability, reduced land usage, lower operational cost, and waste recycling 34 . Therefore, it is difficult to find efficient treatment technologies for the dyeing industries to meet the environmental sustainability requirement.…”
Section: Introductionmentioning
confidence: 99%